POTENSI AGROWISATA BUAH MANGGIS DAN BUAH DURIAN UNTUK KEMANDIRIAN EKONOMI STUDI KASUS DI DESA LUNTO TIMUR DAN LUNTO BARAT KECAMATAN LEMBAH SEGAR KOTA SAWAHLUNTO - Heru Gusti Alrino; Widya Prarikeslan (DEPARTEMEN GEOGRAFI FIS UNP, 2021)
This research discusses what steps are being taken to make East Lunto Village and West Lunto Village into mangosteen and durian fruit agro-tourism areas for economic independence, and to find out what methods are taken to increase community income from the potential of mangosteen and durian fruit agro-tourism. the. The approach to this research is primary data, obtained directly through interviews or questionnaires and observations or observations from respondents of mangosteen and durian fruit farmers as well as mangosteen and durian fruit collectors. Meanwhile, secondary data was obtained through recording data in various agencies. The data analysis technique uses SPOT 6 satellite imagery, from this image we will determine the area of ​​the mangosteen and durian fruit plantations. This study can be concluded that the potential of agrotourism in the village of East Lunto and the village of West Lunto can be used as an agrotourism area based on the theory of Lothar A. Kreck, and for economic independence the mangosteen fruit and durian fruit can be processed to be made into various types of food and medicines that can be an income for the local community.